Методи та алгоритми прийняття рішень на основі теорії прецедентів у сучасних інформаційних системах - Клименко, Д. А.; Шеховцова, В. І. (ХНУРЕ, 2025)
In modern information systems, an important task is to make effective decisions in complex or uncertain sІТuations. One of the approaches used for this purpose is Case-Based Reasoning (CBR). ІТ is based on analyzing previous cases (precedents) and using them to find the best solutions in new sІТuations. This approach is widely used in artificial intelligence, medical systems, automated consulting systems, and business analytics. The main idea of this method is to use the accumulated experience to find solutions to new problems faster and more accurately based on similar cases from the past.
Keywords: теорія прецеденту; алгоритми прийняття рішень